Addressing sustainability gaps - Ramakrishna, Seeram; Rajan, Jose (Elsevier B.V., 2022)
Widespread industrialization, rapid urbanization, and massive transport through land, waters, and air have led to catastrophes such as climate change, water pollution, resource limitation, and pandemics causing severe economic consequences, massive influences on the natural environment and pose a great threat to the life sustainability. Sustainability topic has a long history, and many policies and initiatives are in effect for a sustainable planet Earth, still gaps of varying degrees exist in almost all sectors. This article addresses the essentiality of minimising the sustainability gaps exist in diverse realms of life and citing few examples. Creating a cyclic path for production–consumption process in the economic sector through promoting circular economy, learning from the natural processes through appropriate biomimicking, and knowledge-integration from diverse disciplines and emphasizing sustainability in the educational sector are shown to lower the sustainability gaps.